ENT 530 Social Media Portfolio: Mamasabya / Nur 'Ain Nadhirah Mohd Syamsul Anuar - Mohd Syamsul Anuar, Nur 'Ain Nadhirah (2021)
For the executive summary for my business that I give a name Mamasabya that stand for “Mamasab” product, “bya” is by ‘Ain. The purpose of this business is to help the employees to gain some money and get more knowledge about business. To be more specific, Mamasab International Sdn Bhd is an organization that sells the desserts and some other things such as towel and contact lens. Mamasab International Sdn Bhd use a dropship system and I am one of the dropship. In 2020, Mamasab International Sdn Bhd now already have 12 outlets in Malaysia and have a target to open more outlet for 2021. The founder of Mamasab International Sdn Bhd is Puan Siti Sabrina Binti Sabri or more known as Mama Sabrina or MamaSab. A long time ago, she is the radiographer for the government hospital in Lembah Klang. She start to sells the cake on 2015 in her own home in Klang. This Mamasab International Sdn Bhd wants to help the other who wants to start a business with no modal and we just have to promote and settle down the delivery for our customers. Mama Sabrina always said that she wants to help the other to do some business or people who wants to become an excellent businessmen or businesswomen like her. This organization have many dessert such as Brownies, Congo bars, Nutella Oat Bar, Pandan Gula Melaka cakes, Nutella Cheese Tart, the cosmetics such as gentle face wash and many more. For being the agent, I finally can get my own dropship or to be more specific, the person who will get in charge by me. I have a few dropships and I like to draw my organization chart on this portfolio. In conclusion, I make this business to help my employees or my dropship to become an excellent businessman. The other conclusion is I want people to see Mamasab business as an good opportunities to get a more knowledge about a business. No pain no gain. We have to always trying to get want we wat or else we can not get it.